(untitled) (ModaPalavra e-periódico, 2021)
The presence of plastic microfibers in the ocean is a complex problem that requires urgent solutions. Recent research has shown that one of the sources of these tiny particles is associated with synthetic fabrics intended for making clothes. Collecting them from aquatic environments is an almost impossible task. The solutions, per hour, depend on actions that minimize the emissions of these particles. This study brings together 2 proposals to better understand them and raise their pros and cons.